Creative Cultural Synergy: Towards the Africa of the Future - Ogar, Tom Eneji; Edor, Edor John (PINISI Discretion Review, 2020)
In this paper, we discussed Creative Cultural Synergy: Towards the Africa of the Future in ensuring an enduring development in a competitive and globalized world. Africa today is far from being a viable continent – as most social institutions that should regulate socio-political life are weak and human instincts predominate individual conduct. As a result, the task of nation building has become a mirage. Rather than see these problems within their larger social and cultural context, people tend to place hope on reforms with narrow economic focus. The issue of the African future in African philosophy is that of how best to achieve freedom and development in Africa without compromising the African identity. Defining the African project today is situated in the cultural confusion generated by the assault on the consciousness of its people. Several narratives have been put forward to explain this malaise. This paper concludes that there is need for a cultural and reconstructive examination as a tool in African philosophy to set up the Africa of the future. A creative cultural synergy using some aspects of the African culture with that of others would guarantee its cultural autonomy without setting apart from others in their quest for development. Textual and content analysis approaches are adopted in this research.